ANALISIS SISTEM ANTRIAN PELAYANAN NASABAH BANK X KANTOR WILAYAH SEMARANG - Prizka Rismawati Arum; Sugito Sugito; Yuciana Wilandari (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Waiting is very boring for many people because it will only waste a lot of their time. This situation is common happen in a queue, for example customers who will conduct the transaction in the bank. Bank X Semarang Regional Office is the largest branch of Bank X is in Semarang is also not free from this problem. Therefore, the queuing model search is very important in order to improve the quality of service to customers / clients. Based on the analysis of data in the Customer Service and Teller obtained the appropriate queuing models which, for Customer Service and Public Teller queuing model is (M / M / 6): (GD / ∞ / ∞) queuing model for the Teller Express is (M / M / 2): (GD / ∞ / ∞) and for Special Teller model of the queue is (M / G / 1): (GD / ∞ / ∞). Based on the calculations and analyzes that have been done, it can be concluded that the customer service system to the Customer Service and teller at Bank X Semarang Regional Office has been good. Keywords: Queue, Queuing System Model, Bank, Customer Service, Teller.